Collection grading and evaluation of cumulus-oocyte-complexes for in vitro maturation in sheep (Bangladesh Veterinarian, 2011)
An alternative to superovulation is in-vitro production (IVP) of embryos where the efficient collection and grading of oocytes is important. Ovaries from an abattoir were collected and categorized as type I with no corpus luteum (CL), and type II with CL. The length, width and weight of type I and type II ovary were 1.4 ± 0.03 and 1.5 ± 0.08 cm; 0.8 ± 0.04 and 1.0 ± 0.07 cm; 0.6 ± 0.07 and 0.7 ± 0.04 gm, respectively, each significantly (P0.05). The number of normal (1.9 ± 0.11) and total (2.5 ± 0.14) COCs per ovary were significantly (P